Makna Ritual Dalail Al-Khairat bagi Pelaku Usaha Batik di Masjid Ar-Rahman Kradenan Kota Pekalongan - Irfan Miftahul Fitri (JOUSIP: Journal of Sufism and Psychotherapy, 2021)
The phenomenon of the emergence of spiritual excitement among batik business actors is a symptom due to economic influences, the search for peace of life, desire for a better life, as a support for smooth business and so on. This is a phenomenon of urban Sufism which is marked by the emergence of assemblies of dhikr and shalawat in urban areas. This study aims to determine the background and meaning of the Dalail Al-Khairat Tradition at the Ar-Rahmah Mosque for Batik Businesses at the Ar-Rahmah Kradenan Mosque, Pekalongan City. This type of research is a qualitative method with a phenomenological approach. Data collection techniques in this study used interviews and direct observation. All data were analyzed using descriptive analysis method. The results of the study show that the Jama'ah who follow the Dalail Al-Khairat tradition at the Ar-Rahmah Kradenan mosque consist of various groups, but are dominated by batik businesses in the city of Pekalongan and its surroundings. They come to the Ar-Rahmah mosque with various background problems experienced, such as family encouragement, love to read prayers, environmental factors, desire to live a better life, so that business runs smoothly, and get intercession from the Prophet Muhammad SAW. The Dalail Al-Khairat tradition at the Ar-Rahmah Kradenan mosque provides a lot of meaning for batik business actors who regularly participate in these activities. The meanings obtained when following the Dalail Al-Khairat tradition include peace of mind, sharing, discipline, blessing and the emergence of a sense of mahabbah.